Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the given equation step by step, let's start by simplifying the expression inside the brackets and the braces.
Given equation:
[tex]\[ x - \{2 + [x - (3x - 1)]\} = 2 - x \][/tex]
First, simplify the innermost expression [tex]\( 3x - 1 \)[/tex]:
[tex]\[ x - (3x - 1) = x - 3x + 1 = -2x + 1 \][/tex]
Now substitute this back into the equation:
[tex]\[ x - \{2 + [ -2x + 1 ]\} = 2 - x \][/tex]
Next, simplify inside the brackets:
[tex]\[ 2 + [ -2x + 1 ] = 2 - 2x + 1 = 3 - 2x \][/tex]
Now substitute this back into the equation:
[tex]\[ x - \{3 - 2x\} = 2 - x \][/tex]
Simplify inside the braces:
[tex]\[ x - (3 - 2x) = x - 3 + 2x = 3x - 3 \][/tex]
So now our equation is:
[tex]\[ 3x - 3 = 2 - x \][/tex]
Combine like terms by adding [tex]\( x \)[/tex] to both sides:
[tex]\[ 3x + x - 3 = 2 \][/tex]
[tex]\[ 4x - 3 = 2 \][/tex]
Add 3 to both sides to isolate the term with x:
[tex]\[ 4x = 5 \][/tex]
Finally, divide both sides by 4 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{5}{4} \][/tex]
Thus, the value of [tex]\( x \)[/tex] is [tex]\(\boxed{\frac{5}{4}}\)[/tex].
Given equation:
[tex]\[ x - \{2 + [x - (3x - 1)]\} = 2 - x \][/tex]
First, simplify the innermost expression [tex]\( 3x - 1 \)[/tex]:
[tex]\[ x - (3x - 1) = x - 3x + 1 = -2x + 1 \][/tex]
Now substitute this back into the equation:
[tex]\[ x - \{2 + [ -2x + 1 ]\} = 2 - x \][/tex]
Next, simplify inside the brackets:
[tex]\[ 2 + [ -2x + 1 ] = 2 - 2x + 1 = 3 - 2x \][/tex]
Now substitute this back into the equation:
[tex]\[ x - \{3 - 2x\} = 2 - x \][/tex]
Simplify inside the braces:
[tex]\[ x - (3 - 2x) = x - 3 + 2x = 3x - 3 \][/tex]
So now our equation is:
[tex]\[ 3x - 3 = 2 - x \][/tex]
Combine like terms by adding [tex]\( x \)[/tex] to both sides:
[tex]\[ 3x + x - 3 = 2 \][/tex]
[tex]\[ 4x - 3 = 2 \][/tex]
Add 3 to both sides to isolate the term with x:
[tex]\[ 4x = 5 \][/tex]
Finally, divide both sides by 4 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{5}{4} \][/tex]
Thus, the value of [tex]\( x \)[/tex] is [tex]\(\boxed{\frac{5}{4}}\)[/tex].
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.